Stepping Together with the Batik Village Community: A Journey of Dedication and Learning - Muhammad Yunus Ahmad Khalqi Kamal, Amanda Fayza Anwari, Auni Azhima, M. Faqih Addin, Nur Sa’adah, Pu (UMBanjarmasin, 2024)
This article documents the community service program implemented by UM Banjarmasin students in Batik Village. The main objective of this program is to improve the quality of life and health of the community, with a special focus on stunting prevention, improving children's nutrition and dental health, and developing creativity and art. The approach used in this activity is a combination of qualitative and quantitative methods, which includes surveys, interviews, observations, workshops, and interactive activities with the community. The results of the program showed an increase in community awareness and understanding of the importance of nutrition and health, as well as the development of children's skills and creativity. The article also provides recommendations for future program improvements, including increased collaboration, use of technology, and active community involvement. This program has demonstrated how a holistic and participatory approach in community service can have a significant impact on the development of the Batik Village community.